Aspects of the Quality Evaluation in the Organizations at the Sheltered Labour Market - Šimonová, Stanislava; Horáková, Lenka (International Business Information Management Association-IBIMA, 2019)
Evaluation of the quality of the performance and production is necessary for marketing of every organization, management monitors quality and thrift of the production. The requirement for the quality improvement of the performance is part of the defined standards, complex methods and tools, which are recommended and used for the quality management. Used methods and principles include the aspect of employees as part as the overall quality of the evaluation of the organization performance; it is part of the employees performance, their management and also their satisfaction. They are the organizations, at which are not strictly possible to use these usual methods and principles. Those are the organizations, which are put into sheltered labour market. Mainly, the organizations with the status of the sheltered workshops, which employ mostly the disabled employees. These specific employment conditions and connected character of the production also requires specific judgement of the quality performance. This text identifies the aspects of the quality evaluation focused to sheltered workshops with disabled employees and describes their realization within the case study in the selected organization at the sheltered labour market.
Aspekty hodnocení kvality v organizacích na chráněném trhu práce
Keywords: Quality Evaluation; Sheltered Workshop; Disabled Employees